UV (ultraviolet) curing pressure-sensitive adhesive for adhesion with low surface energy as well as preparation method and application of UV curing pressure-sensitive adhesive
UV cured pressure-sensitive adhesive prepared by using monomers such as silicone modified acrylate and polyethylene glycol modified acrylate, the problem of poor adhesion performance of low surface energy materials is solved, significantly improved adhesion performance and overall performance, and expanded the application range.
Patent Information
- Application Number
- CN202411829854.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-25
AI Technical Summary
The difficulty in effectively bonding low-surface energy materials such as polyethylene, polypropylene and polytetrafluoroethylene has resulted in limited applications in industries such as automobiles, furniture and construction.
A high-surface energy adhesion UV cured pressure-sensitive adhesive is prepared by using acrylate copolymer prepared from silicone modified acrylate, polyethylene glycol modified acrylate and other acrylate monomers as the main raw materials, and its molecular structure and polymerization reaction conditions are optimized by introducing crosslinking agents and photoinitiators.
It significantly improves the adhesion and overall performance of UV pressure-sensitive adhesives to low-surface energy materials, and expands its application range in the industrial field.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adhesives, and in particular relates to a UV-curable pressure-sensitive adhesive for low surface energy adhesion, and a preparation method and application thereof. Background Art
[0002] In recent years, the bonding technology of low surface energy plastics (such as polyethylene, isotropic polypropylene and polytetrafluoroethylene) has faced challenges, and surface pretreatment is usually required to increase its surface energy and promote molecular-level interactions between the adhesive and the substrate. Common pretreatment methods include corona treatment, plasma treatment, flame treatment, and application of compatible polymer solutions (primers) to expand the polymer surface and achieve chain entanglement with the plastic substrate. However, these pretreatment processes not only increase process complexity, but also lead to additional costs, thus limiting the widespread application of low surface energy plastics.
[0003] In addition, although traditional pressure-sensitive adhesives have the advantages of small equipment investment, low cost, and environmental friendliness, they are still insufficient in terms of adhesion performance to low surface energy materials. For example, for non-polar plastics such as polypropylene, polyethylene, ethylene-propylene diene rubber and polytetrafluoroethylene, the adhesion effect is poor. This problem significantly limits the application potential of these materials in industries such as automobiles, furniture and construction. Therefore, the development of a new type of UV-curable pressure-sensitive adhesive for low surface energy adhesion has become an important task to improve the current technical status in this field. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies in the prior art, the primary purpose of the present invention is to provide a UV-curable pressure-sensitive adhesive for low surface energy adhesion. The main raw materials of the pressure-sensitive adhesive are acrylate copolymers prepared from silicone-modified acrylate, polyethylene glycol-modified acrylate and other acrylate monomers. While maintaining the advantages of the existing UV curing technology, the pressure-sensitive adhesive significantly enhances its adhesion performance to low surface energy materials, thereby greatly improving the overall performance of the UV pressure-sensitive adhesive and its application range.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0006] Another object of the present invention is to provide an application of the above-mentioned UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A UV-curable pressure-sensitive adhesive for low surface energy adhesion is prepared from the following raw materials: 100 parts by mass of an acrylate copolymer raw material, 0.2-2 parts by mass of a photoinitiator, 0.1-2 parts by mass of n-dodecyl mercaptan, 0.3-1.5 parts by mass of azobisisobutyronitrile, 0.5-2.5 parts by mass of a crosslinking agent and 70-100 parts by mass of ethyl acetate; the 100 parts by mass of the acrylate copolymer raw material is composed of 60-85 parts by mass of a soft monomer, 5-15 parts by mass of a hard monomer, 1-10 parts by mass of a functional monomer, 1-10 parts by mass of an organosilicon-modified acrylate and 1-10 parts by mass of a polyethylene glycol-modified acrylate.
[0009] The soft monomer is a mixture of one or more of isooctyl acrylate, butyl acrylate and 2-ethylhexyl acrylate;
[0010] The hard monomer is one or more mixtures of methyl acrylate, methyl methacrylate, ethyl methacrylate, vinyl acetate and 2-phenoxyethyl acrylate;
[0011] The functional monomer is one or a mixture of acrylic acid and methacrylic acid.
[0012] The organosilicon-modified acrylate is one or a mixture of 3-(methacryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(trimethoxysilyl)propyl acrylate, 3-[tris(trimethylsiloxy)silyl]propyl methacrylate and (3-acryloyloxypropyl)tris(trimethylsiloxy)silane.
[0013] The molecular weight of the polyethylene glycol modified acrylate is ≤2000, and specifically is one or a mixture of polyethylene glycol acrylate, polyethylene glycol methacrylate, polyethylene glycol methyl ether methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol ethoxy acrylate and polyethylene glycol ethoxy methacrylate.
[0014] The crosslinking agent is one or a mixture of diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate and tetraethylene glycol diacrylate.
[0015] The photoinitiator is one or a mixture of 4-acryloxybenzophenone, 4-acryloxyethoxybenzophenone and 4-acryloxy-2-hydroxybenzophenone.
[0016] The above-mentioned method for preparing a low surface energy adhesion UV curable pressure sensitive adhesive comprises the following steps:
[0017] (1) Weigh 60 to 85 parts by weight of a soft monomer, 5 to 15 parts by weight of a hard monomer, 1 to 10 parts by weight of a functional monomer, 1 to 10 parts by weight of an organosilicon-modified acrylate, 1 to 10 parts by weight of a polyethylene glycol-modified acrylate, 0.2 to 2 parts by weight of a photoinitiator, 0.1 to 2 parts by weight of n-dodecyl mercaptan, 0.3 to 1.5 parts by weight of azobisisobutyronitrile, 0.5 to 2.5 parts by weight of a crosslinking agent, and 70 to 100 parts by weight of ethyl acetate, and mix them uniformly to obtain a mixed solution;
[0018] (2) uniformly dropping the mixed solution into the reaction kettle, raising the temperature to 65-90° C. to initiate a free radical polymerization reaction, and maintaining the temperature at 75-90° C. for 2-5 hours after the dropwise addition is completed to obtain a polymer solution;
[0019] (3) The polymer solution is distilled under reduced pressure at a temperature of 120-150° C. to remove ethyl acetate, thereby obtaining a UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0020] Application of the above-mentioned low surface energy adhesion UV curing pressure-sensitive adhesive in hot melt pressure-sensitive adhesive tape products.
[0021] The low surface energy adhesive UV curing pressure sensitive adhesive is melted at 100-140°C, and then heated at 20-65 g / m 2 The coating amount is coated on a film substrate, and light-cured with a 200-408nm ultraviolet light source to obtain a UV-curable pressure-sensitive adhesive tape product for low surface energy adhesion.
[0022] The film substrate is a film substrate such as a PET film or a BOPP film.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] The present invention optimizes the molecular structure of the pressure-sensitive adhesive by introducing a polyethylene glycol-modified acrylate monomer, thereby improving its adhesion and cohesion with the substrate. In the molecular design of the pressure-sensitive adhesive, a low-surface-energy silicone-modified acrylate is added, which significantly enhances the bonding performance to low-surface-energy materials. At the same time, by introducing a cross-linking agent, the cohesive strength is further enhanced, and the holding force is effectively improved. In general, the present invention significantly enhances the adhesion performance to low-surface-energy materials through molecular design while retaining the advantages of existing UV curing technology, thereby greatly improving the overall performance and application range of the UV pressure-sensitive adhesive. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Experimental methods without specific conditions in the examples are carried out according to conventional methods and conditions.
[0026] Method for determining initial adhesion: The loop initial adhesion test of PET pressure-sensitive tape is tested in accordance with GB / T 31125-2014.
[0027] Method for determining peel strength: The peel strength of PET pressure-sensitive tape is tested using a tensile testing machine in accordance with GB / T2792-2014.
[0028] Method for determining the holding adhesiveness: The holding adhesiveness of PET pressure-sensitive tape is tested in accordance with GB / T4851-2014.
[0029] Embodiment 1:
[0030] (1) 60 g of isooctyl acrylate, 20 g of butyl acrylate, 4.5 g of acrylic acid, 5 g of methyl methacrylate, 4.5 g of methyl acrylate, 5.0 g of polyethylene glycol methyl ether acrylate (molecular weight 800), 1.0 g of 3-(methacryloyloxy)propyltriethoxysilane, 0.5 g of n-dodecyl mercaptan, 0.5 g of 4-acryloyloxyethoxybenzophenone, 1 g of azobisisobutyronitrile, 1 g of triethylene glycol dimethacrylate, and 80 g of ethyl acetate were mixed to form a 183 g mixture, and then the mixture was added dropwise to the mixture. The mixed liquid was placed in a 500 ml four-necked flask equipped with cooling reflux, dropping, thermometer and mechanical stirring device, and heated to 80°C for free radical initiated polymerization. After the reaction was initiated, the reaction was exothermic. After the dropping was completed, the temperature was raised to 80-85°C and kept for reaction for 3 hours to obtain an acrylate polymer solution. The solution was further distilled at 120-140°C for 1 hour to remove most of the organic solvent, and then the organic solvent was further removed by reduced pressure distillation at 140°C to obtain a UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0031] (2) The low surface energy adhesive UV curable pressure sensitive adhesive obtained in step (1) was hot melted at 130°C, and then heated at 35 g / m 2 The coating amount of 10 ...
[0032] Embodiment 2:
[0033] (1) 50 g of 2-ethylhexyl acrylate, 20 g of butyl acrylate, 7.5 g of acrylic acid, 10 g of vinyl acetate, 7.5 g of 2-phenoxyethyl acrylate, 3.0 g of polyethylene glycol methyl ether methacrylate (molecular weight 1600), 2.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.3 g of n-dodecyl mercaptan, 0.3 g of 4-acryloyloxyethoxybenzophenone, 0.5 g of azobisisobutyronitrile, 0.5 g of diethylene glycol dimethacrylate, and 70 g of ethyl acetate were mixed to prepare 171.6 g of ethanol. The mixed liquid is then added dropwise into a 500 ml four-necked flask equipped with cooling reflux, dropping, thermometer and mechanical stirring device, and heated to 80°C for free radical initiated polymerization. After the reaction is initiated, the reaction is exothermic. After the dropwise addition is completed, the temperature is raised to 73-80°C and the reaction is kept warm for 4 hours to obtain an acrylate polymer solution. The solution is further distilled at 130-140°C for 1 hour to remove most of the organic solvent, and then the organic solvent is further removed by reduced pressure distillation at 140°C to obtain a UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0034] (2) The low surface energy adhesive UV curable pressure sensitive adhesive obtained in step (1) was hot melted at 120°C, and then heated at 35 g / m 2 The coating amount of 10 ...
[0035] Embodiment 3:
[0036] (1) 50 g of 2-ethylhexyl acrylate, 20 g of ethyl acrylate, 7.5 g of methacrylic acid, 10 g of vinyl acetate, 7.5 g of ethyl methacrylate, 3 g of polyethylene glycol ethoxyacrylate (molecular weight 800), 2.0 g of 3-(trimethoxysilyl)propyl acrylate, 1.0 g of n-dodecyl mercaptan, 1.0 g of 4-acryloyloxyethoxybenzophenone, 1.0 g of azobisisobutyronitrile, 1.0 g of diethylene glycol dimethacrylate, and 90 g of ethyl acetate were mixed to form a 194 g mixed solution, and then the mixed solution was added dropwise into a 500 ml four-necked flask equipped with a cooling reflux, dropping, thermometer and mechanical stirring device, and heated to 80° C. for free radical initiated polymerization. After the initiation reaction, the reaction released heat. After the dropwise addition was completed, the temperature was raised to 73-80° C. and kept for reaction for 5 h to obtain an acrylate polymer solution, and then the organic solvent was further removed by reduced pressure distillation at 140° C. to obtain a UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0037] (2) The low surface energy adhesive UV curable pressure sensitive adhesive obtained in step (1) was hot melted at 120°C, and then heated at 35 g / m 2The coating amount of 10 ...
[0038] Embodiment 4:
[0039] (1) 45 g of isooctyl acrylate, 32 g of butyl acrylate, 7.5 g of acrylic acid, 5 g of 2-phenoxyethyl acrylate, 6.5 g of methyl acrylate, 3 g of polyethylene glycol ethoxy acrylate (molecular weight 2000), 1.0 g of 3-(methacryloyloxy)propyl triethoxysilane, 1.0 g of n-dodecyl mercaptan, 1.2 g of 4-acryloyloxyethoxy benzophenone, 1.0 g of azobisisobutyronitrile, 1.5 g of triethylene glycol dimethacrylate, 80 g of The mixture was mixed with ethyl acetate to form 184.7 g of a mixed liquid, and then the mixed liquid was added dropwise into a 500 ml four-necked flask equipped with cooling reflux, dropping, thermometer and mechanical stirring device, and heated to 80°C for free radical initiated polymerization. After the reaction was initiated, the reaction was exothermic. After the dropwise addition was completed, the temperature was raised to 75-90°C and the reaction was kept warm for 3 hours to obtain an acrylate polymer solution, and then the organic solvent was further removed by reduced pressure distillation at 135°C to obtain a UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0040] (2) The low surface energy adhesive UV curable pressure sensitive adhesive obtained in step (1) was hot melted at 120°C, and then heated at 35 g / m 2 The coating amount of 10 ...
[0041] Embodiment 5:
[0042] (1) 50 g of 2-ethylhexyl acrylate, 20 g of butyl acrylate, 7.5 g of acrylic acid, 10 g of vinyl acetate, 7.5 g of 2-phenoxyethyl acrylate, 2 g of polyethylene glycol acrylate (molecular weight 1000), 3.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.4 g of n-dodecyl mercaptan, 0.4 g of 4-acryloyloxyethoxybenzophenone, 0.6 g of azobisisobutyronitrile, 0.6 g of diethylene glycol dimethacrylate, 1 00 grams of ethyl acetate is mixed into 202 grams of a mixed liquid, and then the mixed liquid is added dropwise into a 500-ml four-necked flask equipped with a cooling reflux, dropping, thermometer and mechanical stirring device, and heated to 80°C for free radical initiated polymerization. After the reaction is initiated, the reaction is exothermic. After the dropwise addition is completed, the temperature is raised to 75-90°C and the reaction is kept warm for 2 hours to obtain an acrylate polymer solution, which is then distilled at 140°C to further remove the organic solvent to obtain a UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0043] (2) The low surface energy adhesive UV curable pressure sensitive adhesive obtained in step (1) was hot melted at 120°C, and then heated at 35 g / m 2 The coating amount of 10 ...
[0044] Comparative Example 1:
[0045] The difference between the comparative example and the example is that no organosilicon-modified acrylate and polyethylene glycol-modified acrylate are added.
[0046] (1) 50 g of 2-ethylhexyl acrylate, 20 g of butyl acrylate, 7.5 g of acrylic acid, 10 g of vinyl acetate, 7.5 g of 2-phenoxyethyl acrylate, 0.4 g of n-dodecyl mercaptan, 0.4 g of 4-acryloyloxyethoxybenzophenone, 0.6 g of azobisisobutyronitrile, 0.6 g of diethylene glycol dimethacrylate, and 100 g of ethyl acetate were mixed to form 202 g of a mixed solution, and then the mixed solution was added dropwise into a 500 ml four-necked flask equipped with a cooling reflux, dropping, thermometer and mechanical stirring device, and heated to 80° C. for free radical initiated polymerization. After the initiation reaction, the reaction was exothermic. After the dropwise addition was completed, the temperature was raised to 75-90° C. and the temperature was kept for reaction for 3 h to obtain an acrylate polymer solution, and then the organic solvent was further removed by reduced pressure distillation at 140° C. to obtain a UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0047] (2) The low surface energy adhesive UV curable pressure sensitive adhesive obtained in step (1) was hot melted at 125°C, and then heated at 35 g / m 2 The coating amount of 10 ...
[0048] Comparative Example 2:
[0049] (1) 49 g of isooctyl acrylate, 32 g of butyl acrylate, 7.5 g of acrylic acid, 5 g of 2-phenoxyethyl acrylate, 6.5 g of methyl acrylate, 1.0 g of n-dodecyl mercaptan, 1.2 g of 4-acryloyloxyethoxybenzophenone, 1.0 g of azobisisobutyronitrile, 1.5 g of triethylene glycol dimethacrylate, and 80 g of ethyl acetate were mixed to form 184.7 g of a mixed solution, and then the mixed solution was added dropwise into a 500 ml four-necked flask equipped with a cooling reflux, dropping, thermometer and mechanical stirring device, and heated to 80° C. for free radical initiated polymerization. After the initiation reaction, the reaction was exothermic. After the dropwise addition was completed, the temperature was raised to 75-90° C. and the temperature was kept for reaction for 2 h to obtain an acrylate polymer solution, and then the organic solvent was further removed by reduced pressure distillation at 140° C. to obtain a UV-curable pressure-sensitive adhesive for low surface energy adhesion.
[0050] (2) The low surface energy adhesive UV curable pressure sensitive adhesive obtained in step (1) was hot melted at 120°C, and then heated at 35 g / m 2 The coating amount of 10 ...
[0051] Table 1: Performance test results of pressure-sensitive adhesive tape examples and comparative examples (25°C)
[0052]
[0053]
[0054] Note: 1) HDPE: high-density polyethylene plate, thickness 3mm; SS: stainless steel plate; 2) - means the test result is too small and the test result is not displayed.
[0055] According to the test results in Table 1, the adhesion performance of the pressure-sensitive adhesive tape is significantly improved with the change of light curing intensity, which expands its application range and product adaptability in the industrial field. The comparison of the adhesion performance of the embodiment and the comparative example on the HDPE surface shows that the embodiment is significantly enhanced in bonding low surface energy materials, residual glue appears on the steel plate in the comparative example, and the adhesion is less than 24 hours. These results are mainly attributed to the molecular structure design of the sample, including the introduction of silicone-modified acrylate, polyethylene glycol-modified acrylate and polyethylene glycol-modified cross-linking agent. By adjusting the flexibility of the molecular chain, reducing the surface energy and optimizing the degree of cross-linking, the adhesion performance to low surface energy materials is significantly improved. With the increase of light intensity, the cohesive strength is enhanced. Although the peel strength and initial viscosity have decreased, the results of the adhesion test are still more than 168 hours. The present invention provides a new idea and possibility for the application of pressure-sensitive adhesives.
[0056] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A UV curable pressure sensitive adhesive for low surface energy adhesion, characterized in that: The pressure-sensitive adhesive is prepared from the following raw materials: 100 parts by mass of an acrylate copolymer raw material, 0.2-2 parts by mass of a photoinitiator, 0.1-2 parts by mass of n-dodecyl mercaptan, 0.3-1.5 parts by mass of azobisisobutyronitrile, 0.5-2.5 parts by mass of a crosslinking agent and 70-100 parts by mass of ethyl acetate; the 100 parts by mass of the acrylate copolymer raw material is composed of 60-85 parts by mass of a soft monomer, 5-15 parts by mass of a hard monomer, 1-10 parts by mass of a functional monomer, 1-10 parts by mass of an organosilicon-modified acrylate and 1-10 parts by mass of a polyethylene glycol-modified acrylate.
2. The low surface energy UV curable pressure sensitive adhesive according to claim 1, characterized in that: The soft monomer is a mixture of one or more of isooctyl acrylate, butyl acrylate and 2-ethylhexyl acrylate; The hard monomer is one or more mixtures of methyl acrylate, methyl methacrylate, ethyl methacrylate, vinyl acetate and 2-phenoxyethyl acrylate; The functional monomer is one or a mixture of acrylic acid and methacrylic acid.
3. The low surface energy UV curing pressure sensitive adhesive according to claim 1, characterized in that: The organosilicon-modified acrylate is one or a mixture of 3-(methacryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(trimethoxysilyl)propyl acrylate, 3-[tris(trimethylsiloxy)silyl]propyl methacrylate and (3-acryloyloxypropyl)tris(trimethylsiloxy)silane.
4. The low surface energy UV curable pressure sensitive adhesive according to claim 1, characterized in that: The molecular weight of the polyethylene glycol modified acrylate is ≤2000, and specifically is one or a mixture of polyethylene glycol acrylate, polyethylene glycol methacrylate, polyethylene glycol methyl ether methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol ethoxy acrylate and polyethylene glycol ethoxy methacrylate.
5. The low surface energy UV curing pressure sensitive adhesive according to claim 1, characterized in that: The crosslinking agent is one or a mixture of diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate and tetraethylene glycol diacrylate.
6. The low surface energy UV curing pressure sensitive adhesive according to claim 1, characterized in that: The photoinitiator is one or a mixture of 4-acryloxybenzophenone, 4-acryloxyethoxybenzophenone and 4-acryloxy-2-hydroxybenzophenone.
7. The method for preparing a UV-curable pressure-sensitive adhesive for low surface energy adhesion according to claim 1, characterized in that The steps include: (1) Weigh 60 to 85 parts by weight of a soft monomer, 5 to 15 parts by weight of a hard monomer, 1 to 10 parts by weight of a functional monomer, 1 to 10 parts by weight of an organosilicon-modified acrylate, 1 to 10 parts by weight of a polyethylene glycol-modified acrylate, 0.2 to 2 parts by weight of a photoinitiator, 0.1 to 2 parts by weight of n-dodecyl mercaptan, 0.3 to 1.5 parts by weight of azobisisobutyronitrile, 0.5 to 2.5 parts by weight of a crosslinking agent, and 70 to 100 parts by weight of ethyl acetate, and mix them uniformly to obtain a mixed solution; (2) uniformly dropping the mixed solution into the reaction kettle, raising the temperature to 65-90° C. to initiate a free radical polymerization reaction, and maintaining the temperature at 75-90° C. for 2-5 hours after the dropwise addition is completed to obtain a polymer solution; (3) The polymer solution is distilled under reduced pressure at a temperature of 120-150° C. to remove ethyl acetate, thereby obtaining a UV-curable pressure-sensitive adhesive for low surface energy adhesion.
8. Use of the low surface energy adhesion UV curing pressure sensitive adhesive according to claim 1 in hot melt pressure sensitive adhesive tape products.
9. The use according to claim 8, characterized in that: The low surface energy adhesive UV curing pressure sensitive adhesive is melted at 100-140°C, and then heated at 20-65 g / m 2 The coating amount is coated on a film substrate, and light-cured with a 200-408nm ultraviolet light source to obtain a UV-curable pressure-sensitive adhesive tape product for low surface energy adhesion.
10. The use according to claim 9, characterized in that: The film substrate is a PET film or a BOPP film.
Citation Information
Patent Citations
Ultraviolet-curable high temperature resistant pressure-sensitive adhesive and preparation method thereof
CN103484042A
Ultraviolet curing pressure-sensitive adhesive containing ultraviolet cross-linked tackifying resin and preparation method thereof
CN104673105A
Multifunctional amphiphilic comb-type polymer modifier, and preparation method and application thereof
CN105542065A
Solvent-free light-cured organosilicone acrylate polymer pressure-sensitive adhesive and preparation method thereof
CN118546290A
Ultraviolet curing solvent-free low-viscosity acrylate polymer adhesive as well as preparation method and application thereof
CN118853033A